Increasing rural employment in sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2012)
Sub-Saharan Africa faces enormous socio-economic challenges, one of the greatest being the lack of work in rural areas. Already, tens of millions of rural Africans have no work, or not enough to lift themselves out of poverty. At the Brussels Development Briefing on ‘Major Drivers for Rural Transformation in Africa: Job Creation for Rural Growth’, experts proposed a range of measures to increase employment. These ‘Policies for Progress’ – as highlighted in this CTA Policy Brief – include: governments introducing policies which stimulate growth of the rural farm and non-farm sectors; governments increasing investment in education and vocational training in rural areas, especially for young people; and small-scale farmers being encouraged to work together to improve productivity and access to markets. Policies should ensure that women, who represent a major workforce in rural areas, receive the same benefits and support as men.